Synthesis, characterization and modelling of nickel nanowires synthesized via template-assisted electrodeposition - Nurhanis Sofiah, Abd Ghafar (2017)
Nanometer-sized structures have attracted lots of interest due to its unique mechanical, electronic, optical, electrical, chemical and magnetic properties; opening up a broad view of the application. Metallic nanowires classified as a nano-sized material with the characteristic length scale in the range of 1-1000 nanometers. As one of the most important one-dimensional (1D) nanostructures, metallic nanowire such as Nickel (Ni) expected to play a vital part in the future. Many synthesis and characterization method have been developed to produce this structures, but due to the nature of this structures which exhibits different behavior at different condition (environmental and synthesis), the comprehensive knowledge of these structures still in its early stages. Apart from that, due to the size of these structures, the well-established macro-scale mechanical characterization technique could not be used to determine the mechanical properties of these structures. As such, the modeling and simulation methods would be the alternate methods to provide further insights into various deformation mechanisms and mechanical properties. Therefore, the objectives of this research are to synthesize Ni nanowires via template-assisted electrochemical deposition technique; and to understand the influence of deposition bath temperature and stabilizer concentration on the physical properties. In this study, the stabilizer concentration was varied from 5 g/L, 37.5 g/L and 60 g/L with the deposition bath temperature of 40 °C, 80 °C, and 120 °C. The morphology, elemental analysis and crystallographic properties were analyzed using FESEM, EDX, and XRD. The elaboration of the physical properties of obtained Ni nanowires by taking into account the effect of stabilizer concentration and deposition bath temperature on the elemental composition, surface morphology, growth length, crystal orientation and crystal size of the synthesized Ni nanowires discussed. The mechanical properties of Ni nanowires are estimated through molecular dynamic (MD) simulation. Key research insight from the present investigation concludes that the template-assisted electrochemical deposition approach successfully synthesized high purity Ni nanowires (97.97% based on EDX analysis). Qualitative analysis from FESEM images showed that all the surface texture of Ni nanowires found to be rough and flaky with rough surface texture when the deposition temperature increase. XRD analysis suggests that all the grown Ni nanowire is polycrystalline in nature and the obtained XRD spectrum does not show any change in the crystal orientation when different synthesis condition was applied. However, increase in crystal size was noticed when deposition temperature increased, and it is also noted that the average of crystal size increase in small amount when the stabilizer concentration reduced. From MD simulation, the estimated elastic modulus for Ni nanowires is between 140.02 to 142.5 GPa, the yielding stress between 16.465 to 16.732 GPa and the yielding strain between 0.1181 to 0.1209. The present research contributes to the understanding the influence of processing parameter towards the physical properties of metallic nanowires, as well as designing experimental procedure for future extension to other nanomaterials.